Emotional Skills Training to Control Aggression and Increase Social Adaptation in Children with Educable Mental Retarded - Falah Nodehi , Masoumeh; Khorasani, Zahra; Sadat Masjedi, Fatemeh; Farhadi , Azimeh; Ghorbani, Morteza (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: Children with educable mental retardation encounter difficulties in acquiring knowledge, social skills, and managing their feelings. This current research aims to instruct emotional skills to control aggression and enhance social adaptability in children with educable mental retardation. Methods and Materials: The current research is an applied and quasi-experimental study that includes a pre-test, post-test, and a follow-up phase of three months with both a control and experimental group. The statistical population for this study was mentally retarded children aged nine to thirteen years’ old who were attending special education centers during the summer and fall of 2023 in Tehran. The sample consisted of 32 individuals (16 in the experimental group and 16 in the control group) chosen through purposive sampling. Educational sessions lasting 60 minutes each were conducted twice a week, totaling seven sessions. The assessment tools used were the Child Aggression Scale (CAS) and the Rutter Child Behavior Questionnaire (RCBQ). Data analysis was performed using SPSS version 27 software, employing descriptive statistics (mean and standard deviation), repeated measures covariance analysis, Bonferroni post hoc test, and Kruskal-Wallis H test at a -value of 0.05. Findings: According to the research results, the p-value for Between-Subjects Effects comparing the experimental and control groups regarding aggression and parental perspective on aggression was statistically significant (p